Identification of Stomata Types in Plants of The Genus Saccharum - Syabrina, Annisa; Anjani, Diyah; Selvira; Nuriyati; Sarjani, Tri Mustika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Stomata are openings in the epidermis that are lined by two special epidermal cells known as guard cells. In sugarcane (Saccharum officinarum) leaves, stomata are found on both the upper (adaxial) and lower (abaxial) surfaces, making them amphistomatous. Stomata are classified into several types, including anomocytic, anisocytic, and parasitic. Studies on the structure of stomata in plants of the genus Saccharum are still limited. This study aims to provide scientific information about the types of stomata in Saccharum plants. This study was carried out from October to November 2023 at the biology laboratory. Qualitative descriptive method with the type of stomata considered under the microscope. Data collection techniques using observation. The results of this investigation show that the genus Saccharum has Graminae type stomata, guard cells shaped like a halter. Stomata size in sugarcane species is generally larger than in barnyard grass species.